Corporate blockholders and financial leverage. Issue 3 (7th June 2022) - Bui, Thuy
Abstract: This research investigates the relation between corporate blockholders and firm financial leverage. Corporate blockholders—nonfinancial firms who hold more than five percent equity in another company—might affect firm policies through their business relations, monitoring, or expropriations. I find that corporate block ownership is negatively related to the target firm's leverage. Moreover, the negative association between corporate blocks and leverage becomes stronger when these investors have greater board representation and when the firm has higher agency costs. Overall, my findings suggest that corporate blockholders play an important monitoring role and can substitute for other monitoring mechanisms, including leverage